The effect of an evidence-based management plan on upper limb and trunk lymphoedema, function and quality of life in breast cancer survivors : a series of N=1 studies - Way, Liesl (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScPhysio)--Stellenbosch University, 2022.